Feminism Critical of Semusim Dan Semusim Lagi Novel by Andina Dwifatma - Hafid, Abdul (INTERACTION: Jurnal Pendidikan Bahasa, 2020)
The study is intended to describe a feminist critique of the novel Semusim, dan Semusim Lagi by Andina Dwifatma. This type of research is qualitative with a social feminist approach. The main source of data in this study is the novel Semusim, dan Semusim Lagi by Andina Dwifatma. Technique of collecting data used literary techniques. Technique of data analysis used analytic descriptions. Novel Semusim, dan Semusim Lagi by Andina Dwifatma is the revealing of the wide variety of women's issues in society. Uncovering the construction built by the public against women. It also implied teaching and displaying attitudes of life and ideology to women. The weakness/criticism of the Semusim, dan Semusim Lagi by Andina Dwifatma is that of the writer, which directs the female struggle toward liberal feminists, such as the freedom of women to be free from children. Deconstructing the social view of women done by authors is sketchy.